Evaluating a Digital Literacy Program for Misinformation Discernment and Digital Civil-Rights Awareness Among Vocational-School Adolescents - Fitri Fitri; Iqbal Syafrudin; Mitra Mustaricha (Jurnal Evaluasi Pendidikan, 2026)
Digital literacy programs are increasingly used to strengthen misinformation discernment and responsible participation in digital environments, yet their evaluation may be distorted when participants begin with near-perfect knowledge scores. This study evaluated the immediate outcomes of a digital literacy program delivered to vocational-school-aged adolescents in Nambo and Lulut, Bogor Regency, Indonesia. The program combined conceptual instruction, case-based identification of misinformation, guided use of verification tools, discussion of digital rights and responsibilities, and an invitation to participate as digital-literacy agents. A one-group pretest-posttest evaluation was conducted on 18 June 2026. Of 20 pretest and 20 posttest responses, 19 valid identity-matched pairs were analyzed. Participants were 15-18 years old (M = 16.42, SD = 0.69). The ten-item assessment measured knowledge of digital literacy, misinformation, source verification, digital civil rights, hate-speech responses, personal-data protection, and digital ethics. Mean scores increased from 98.42 (SD = 6.88) to 99.47 (SD = 2.29). The Wilcoxon signed-rank test did not indicate a statistically significant aggregate change (p = .317, r = .229), largely because 94.7% of participants had already achieved the maximum score at pretest. Eighteen scores remained at 100, whereas one participant improved from 70 to 90. Item-level gains occurred in appropriate responses to hate speech and understanding the purpose of digital literacy. The program is therefore best interpreted as maintaining high competence while producing targeted improvement, rather than generating a broad score increase. Future evaluations should use more demanding performance tasks, delayed posttests, and behavior-based indicators to improve measurement sensitivity and establish retention and transfer.